The Characterization Adaptation in and “Then There Were None” - Ramdani, Paisal; Saehu, Andang; Pramita, Agry (Universitas Negeri Padang, 2023)
This study analyzes the adaptation process of literary element in the novel and the film “And Then There Were None” by Agatha Christie. The researcher uses a qualitative descriptive method combined with Huctheon theory because the research results and the content of this study are in the form of words and pictures that must be explained and referred to as content analysis. Theory of Literary Adaptation by Hutcheon uses to review the data where the discussion focuses on character & characterization as a literary element in the novel and the film And Then There Were None by Agatha Christie. This study provides new results regarding the changes in character & characterizations in the novel to the film. One adaptation process found in this research is subtraction, which relates to the omission of the novel’s character in the film form. In this case, the adaptation process refers to the character's peripheral roles. The peripheral role of the character is a type of character that is unimportant or unnecessary to the core of the story. This research also provides another type of adaptation process, namely modification related to the character's characterization in the film form.